Mortality after admission with pneumonia is higher than after admission with an exacerbation of COPD. Issue 5 (19th May 2022) - Vestbo, Jørgen; Waterer, Grant; Leather, David; Crim, Courtney; Diar Bakerly, Nawar; Frith, Lucy; Jacques, Loretta; Harvey, Catherine; Satia, Imran; Woodcock, Ashley
Patients with COPD often experience exacerbations and pneumonia that are occasionally severe and lead to hospital admission [1–3]. The risk of pneumonia is further increased by treatment with inhaled corticosteroids (ICS) [4–6]. Although potentially difficult to distinguish [7], there could be differences in the risk of death associated with these events that need to be taken into account when planning management and clinical follow-up. The Salford Lung Study was set up to evaluate the effectiveness and safety of the once-daily inhaled combination of fluticasone furoate and vilanterol (FF/VI; in ELLIPTA dry powder inhaler) compared with existing maintenance therapy (usual care) in a large, real-world population of patients with COPD in conditions of normal care [8]. Strengths of the study include the relatively unselected patient population, the completeness of follow-up using a joint electronic record system and the fact that all patients were provided usual standard of care for their exacerbations and during admissions. We used this study database to examine mortality after an admission with a severe exacerbation or pneumonia, and the impact of classification of these events. Mortality after an admission for pneumonia is considerably higher than for an admission for an exacerbation in COPD patients recruited from usual clinical practice. A proper diagnosis in acute worsenings of symptoms in COPD is therefore important. https://bit.ly/3LyhnnC